Carbon and oxygen isotopic variations in early Albian limestone facies of the Mural Formation, Pitaycachi section, northeastern Sonora, Mexico - Madhavaraju, Jayagopal; Sial, Alcides; González-León, Carlos; Nagarajan, Ramasamy (Universidad Nacional Autónoma de México, 2013)
We used petrofacies analysis and stable isotope data to interpret the isotopic variations in the marine carbonate succession of the Early Cretaceous Mural Formation of northeastern Sonora (Pitaycachi section), Mexico. The petrographic study reveals a range of lithofacies from bioclastic mudstones to boundstones. Allochems consist of corals, algae, rudists, echinoids, sponge spicules, radiolarians, foraminifera and calpionellids. Samples analyzed for stable isotope are significantly depleted with d18Ovalues of -15.19‰ to -6.32‰ and exhibit positive δ13C values ranging from 2.91‰ to 4.39‰. The lack of correlation between δ13C and δ18O values also supports a primary marine origin for the δ13C values of limestones from the Pitaycachi section. In the d13C profile, the Cánova Member shows an upward increasing trend from 3.09‰ to 4.36‰ interpreted to indicate an increase in the rate of marine organic production and/or organic burial in the basin during early Albian time. The abrupt increase in carbon isotope values in the lower part of the section correlates with OAE1b. The shape of the C-isotope curve of the present study is similar to other C-isotope curves from Mexico and other continents (e.g., Vacontian basin, France) indicating that OAE1b may have been global in extent.